Evaluation and Improvement of User Interface Design in Mobile Delivery Services With User Centered Design Approach and Heuristic Evaluation (Case Study: Kirimaja Application) - Ardhani, Ni Komang Sucitra; Wirdiani, Ni Kadek Ayu; Rusjayanthi, Ni Kadek Dwi (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2023)
KirimAja is a mobile-based goods delivery service application that is useful for helping people to send goods easily. This application has several features for sending goods, such as the Sameday Service, Nextday Service, Regular Service, Check Rates, and Check Receipts features. Usability problems in the KirimAja application were found based on observations and responses found in the "Google Play Store" and "App Store", namely in an unattractive appearance and display of error messages that were not well understood, therefore a usability evaluation and improvement of the user interface design are needed help the user when using the application. Evaluation and improvement of the user interface design in the KirimAja application uses the User Centered Design approach and the Heuristic Evaluation method, while testing user satisfaction with the KirimAja application uses the System Usability Scale method. The design improvements made resulted in increased results, namely by using the Heuristic Evaluation method to get scores on the H5 Error Prevention and H9 Help Users Recognize, Diagnoze, and Recover from Errors aspects from 2 to 0, while using the System Usability Scale method experienced an increase in the grade scale from D to A .